2021
DOI: 10.1128/mra.00215-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Arcanobacterium phocisimile Strain DSM 26142, Isolated from a Harbor Seal

Abstract: Bacteria of the genus Arcanobacterium can be found in a variety of hosts. The species Arcanobacterium phocisimile was originally identified in a free-living harbor seal in the German North Sea in 2004. Here, we announce the complete genome sequence of Arcanobacterium phocisimile strain DSM 26142.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In harbor seals and other marine mammals, Arcanobacterium phocae is widespread and sometimes associated with wound infections ( 6 , 7 ). Routine microbial diagnostic investigations performed as part of a program monitoring harbor seals in the German North Sea revealed that harbor seals also appear to be a natural reservoir for other Arcanobacterium species, as three novel species were identified—namely, Arcanobacterium phocisimile ( 8 , 9 ), A. buesumense ( 10 , 11 ), and A. pinnipediorum ( 1 , 12 ).…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…In harbor seals and other marine mammals, Arcanobacterium phocae is widespread and sometimes associated with wound infections ( 6 , 7 ). Routine microbial diagnostic investigations performed as part of a program monitoring harbor seals in the German North Sea revealed that harbor seals also appear to be a natural reservoir for other Arcanobacterium species, as three novel species were identified—namely, Arcanobacterium phocisimile ( 8 , 9 ), A. buesumense ( 10 , 11 ), and A. pinnipediorum ( 1 , 12 ).…”
Section: Announcementmentioning
confidence: 99%
“…genomes available at NCBI. All genomes were locally annotated using Prokka v1.1.3 ( 18 ), and a maximum likelihood phylogenetic tree was constructed by amino acid sequence comparison of 107 single-copy core genes using bcgTree v1.1.0 ( 19 ) as previously described ( 9 ). The resulting phylogenetic tree ( Fig.…”
Section: Announcementmentioning
confidence: 99%